Bottle tops : the art of El Anatsui - Goldberg, Alison (Lee & Low Books, 2022)
Presents a non-fiction picture book chronicling the life of Ghanaian artist El Anatsui, who creates handmade sculptures from discarded bottle tops, and details his early life, creative process, and impact on contemporary African art. Includes author's note, an activity, and additional resources.